EXPLORING LINEARITY AND TYPES OF SELF-CORRECTIONS IN THE TRANSLATION OF STUDENT TRANSLATORS - Rudy Sofyan; Rusdi Noor Rosa (UNIB Press, 2023)
Considering the importance of correction (post-drafting phase) in translation process, this study aims at finding the linearity and types of self-corrections done by student translators in completing their translation tasks. Three students majoring translation studies who, in this study, were called student translators, were selected as the participants using a purposive sampling method. They were selected based on their relatively homogeneous profile following their linguistic competence including Test of bahasa Indonesia proficiency (UKBI), Test of English proficiency (TOEFL), and Test of typing speed by using TQ (TypingQueen) typing test. In the process of data collection, they were asked to translate two texts from English into bahasa Indonesia. The translation process was recorded using Translog and screen recording (Camtasia Studio 8). In doing their tasks, they were allowed to use online dictionaries and resources. The results of this study show that eight types of self-corrections were done by the student translators, including deletion, word substitution, spelling, return, addition, meaning, capitalization, and grammar, among which word substitution was most frequently used. This study also found types of word deletion that include deleting (i) unnecessary words, (ii) unnecessarily added words, (iii) incomplete words, (iv) repeated words, (v) miscollocation, and (vi) redundancy.